Hook Plate for Volar Rim Fractures of the Distal Radius: Review of the First 23 Cases and Focus on Dorsal Radiocarpal Dislocation - Biondi, Marco; Keller, Marco; Merenghi, Letizia; Gabl, Markus; Lauri, Giulio (Journal of Wrist Surgery, 2019)
Background Fragment-specific fixation of the distal radius is born to fix each articular fragment with limited surgical approach and low-profile devices. Over time, many devices with different designs and characteristics have been developed. However, many of them have showed the inability to securely fix marginal, small, and comminuted fragments as bony ligament avulsions and bony compression injuries.Purpose The purpose of this study was to evaluate the clinical and radiological outcome of a new device born to treat marginal articular fractures of the distal radius.Patients and Methods A retrospective review was conducted on 23 patients with a mean follow-up of 21 months including postoperative clinical evaluation, grip strength, computed tomography scan, and X-ray control.Results All fragments healed and maintained reduced until the final follow-up. The carpus was aligned with the distal radius in all patients presenting with a radiocarpal dislocation.Conclusion The volar rim fragment is an attachment site for the short radiolunate and the volar distal radioulnar ligament. Its unstable fixation can lead to articular incongruity, volar or dorsal subluxation of the carpus, and distal radioulnar instability. The involvement of this fragment on distal radius fractures is relatively common and many studies of the literature have been focused on its treatment. The Hook Plate stabilizes distal fragments at their bone–ligament interface. In addition to bony reduction, the device permits to stabilize the capsule and ligaments, as volar bony ligament avulsions, in a picture of dorsal radiocarpal dislocation.Level of Evidence This is a Level IV, case series.
Keywords: volar rim; hook plate; radiocarpal dislocation; distal radius fractures; volar locking plate